Origin and evolution of SINEs in eukaryotic genomes - Kramerov, D A; Vassetzky, N S (Heredity, 2011)
Short interspersed elements (SINEs) are one of the two most prolific mobile genomic elements in most of the higher eukaryotes. Although their biology is still not thoroughly understood, unusual life cycle of these simple elements amplified as genomic parasites makes their evolution unique in many ways. In contrast to most genetic elements including other transposons, SINEs emerged de novo many times in evolution from available molecules (for example, tRNA). The involvement of reverse transcription in their amplification cycle, huge number of genomic copies and modular structure allow variation mechanisms in SINEs uncommon or rare in other genetic elements (module exchange between SINE families, dimerization, and so on.). Overall, SINE evolution includes their emergence, progressive optimization and counteraction to the cell's defense against mobile genetic elements.